2003
DOI: 10.1080/0142159031000137409
|View full text |Cite
|
Sign up to set email alerts
|

Students' perspectives on the educational environment, Faculty of Medical Sciences, Trinidad

Abstract: The Dundee Ready Education Environment Measure (DREEM) was administered to 70 final-year medical students and 36 first-year medical interns (pre-registration house officers). The overall total mean DREEM scores for the five subscales-namely, students' perceptions of the atmosphere, students' perceptions of learning, students' social self-perceptions, students'perceptions of teachers and students' academic self-perceptions-was 109.9 and the total mean scores for the subgroups-male students, male interns, female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
168
8
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(215 citation statements)
references
References 1 publication
26
168
8
13
Order By: Relevance
“…Our DREEM overall mean score was higher than that reported for medical schools in Faculty of Medical Sciences, Trinidad (109.9) [18], Srilanka (108) [19], India (107.44) [20], King Faisal Medical School Saudi Arabia (111) [21], Umm Al-Qura University (107) [16], King Abdul Aziz University Saudi Arabia (102) [17], Sana'a University (100) [17], Al-Yemen University (99) [22], Canadian Memorial Chiropractic College (97) [23], King Saud University (89.9) [24].…”
Section: Discussioncontrasting
confidence: 86%
“…Our DREEM overall mean score was higher than that reported for medical schools in Faculty of Medical Sciences, Trinidad (109.9) [18], Srilanka (108) [19], India (107.44) [20], King Faisal Medical School Saudi Arabia (111) [21], Umm Al-Qura University (107) [16], King Abdul Aziz University Saudi Arabia (102) [17], Sana'a University (100) [17], Al-Yemen University (99) [22], Canadian Memorial Chiropractic College (97) [23], King Saud University (89.9) [24].…”
Section: Discussioncontrasting
confidence: 86%
“…15,16,29,38,40,44 However, with individual items, there were statistical differences between female and male students for three items. Women perceived the items "the enjoyment outweighs the stress of studying chiropractic" and "my accommodation is pleasant" with higher negativity than males.…”
Section: Specific Implicationsmentioning
confidence: 89%
“…41,42 Guthrie et al 43 reported that, even in the early years of health care education, up to 50% of students' stress is related to aspects of the course work. Bassaw et al 15 have argued that students must be supported all the way through the educational path, from entering school to qualifying and beyond. An educational institution requires a student-friendly atmosphere where high criterion academic support is effortlessly accessible.…”
Section: Specific Implicationsmentioning
confidence: 99%
See 2 more Smart Citations